Pelatihan Analisis Butir Soal dan Analisis Kemampuan Peserta Ujian Bagi Guru Madrasah di Pondok Pesantren Budi Utomo Surakarta - Amin, Lailla Hidayatul; Nashir, Muhammad Ja'far; Subando, Joko Subando; Rohimah, Siti Rohimah (LP2M Universitas Muhammadiyah Enrekang, 2023)
The aim of community service is to equip training participants with question item analysis and test taker ability analysis. The service was carried out at PP Budi Utomo with a total of 35 participants. The service method uses presentations, discussions and simulations, the supporting instruments needed for service are training materials and pre-test and post-test instruments. Data resulting from understanding the training material were analyzed using tests to see the effectiveness of the training. The results of the training showed a significant increase in understanding before and after training regarding evaluation. Post-training recommendations are expected for participants to be able to apply understanding from training activities in their respective schools.